ANALISIS FAKTOR PEMELIHARAAN BANGUNAN GEDUNG DAN PENGARUHNYA TERHADAP KENYAMANAN KEGIATAN PERKULIAHAN DI FAKULTAS TEKNIK UNIVERSITAS KHAIRUN - Ahadian, Edward Rizky; Pengo, Filadelfia; Saputra, Muhammad Taufiq Yuda; Samudra, Annisa Rimadantia (Fakultas Teknik Universitas Khairun, 2025)
Good and correct maintenance of building facilities and infrastructure is very important to ensure optimal service life. In the world of construction, building maintenance serves to maintain the sustainability of the function and condition of the building itself. The results of this maintenance effort will be felt by building users in the form of comfort while doing activities in it. Khairun University (Unkhair) located in Ternate City has various lecture buildings designed to provide comfort to students during the learning process. Every building that is built certainly requires maintenance so that it is maintained and can be used according to its function, so that students can carry out their activities comfortably. The purpose of this study is to measure how much influence building maintenance factors have on comfort in lecture activities at the Faculty of Engineering, Khairun University. In addition, this study also aims to identify the most dominant building maintenance factors that affect the comfort of students as building users in the faculty.Primary data was collected through questionnaire distribution to 242 students using random sampling method. While secondary data related to the number of respondents and other supporting information was obtained from literature and journal studies. Data processing was carried out using the Multiple Linear Regression Analysis method. The results of the study showed that the building maintenance component variable (X) simultaneously had a significant effect on the college comfort variable (Y) with a coefficient of determination of 0.557. This means that the building maintenance variable has an influence of 55.7% on college comfort, while the remaining 44.3% is influenced by other factors not revealed in this study. The most dominant building maintenance factor affecting student comfort is the maintenance of the water system, with a Beta value of 0.236.